Analisis Sastra Siber Puisi Aku Ingin Karya Saut Situmorang Menggunakan Pendekatan Objektif pada Platform Wattpad - Alif Abdur Rafi Deriansyah; Listia Rizkiyani; Bayu Agustian (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The literary work of poetry, whether in cyber form or not, is inseparable from the activity of analysis. Poetry can be examined from various aspects, one of which is through an objective approach that focuses on the structural elements that build the poem itself. However, cyber literature, as a product of literary development that utilizes digital media for dissemination, has its own uniqueness in its analysis, such as the poem Aku Ingin by Saut Situmorang, which is presented on the Wattpad platform. The analysis not only examines the internal aspects of the poem but also includes cyber elements such as hyperlinks and hypertext. This study aims to provide an in-depth understanding of the structure or elements that construct the poem, as well as the hypertext and hyperlinks embedded within it. The research method used is a qualitative descriptive method with an objective poetry analysis approach. The physical structure of the poem Aku Ingin by Saut Situmorang includes the poem’s form, diction, concrete words, figurative language, and imagery. Meanwhile, its inner structure consists of theme, tone, atmosphere, and message. The cyber elements in the poem include hyperlinks and hypertext. This study concludes that the poem Aku Ingin by Saut Situmorang contains several key components that make it dense and cohesive, both in terms of physical and inner structure. Additionally, the poem can be categorized as cyber literature because it implicitly contains hypertext that establishes intertextuality with the legendary love story of Romeo and Juliet and the poem Aku Ingin by Sapardi Djoko Damono. Its presence on the Wattpad platform also enables interactivity between readers and the author.